Quasilinear degenerate elliptic unilateral problems. (31st January 2005) - Aharouch, L.; Akdim, Y.; Azroul, E.
Abstract : We will be concerned with the existence result of a degenerate elliptic unilateral problem of the formA u + H ( x, u, ∇ u ) = f, whereA is a Leray-Lions operator fromW 1, p ( Ω, w ) into its dual. On the nonlinear lower-order termH ( x, u, ∇ u ), we assume that it is a Carathéodory function having natural growth with respect to| ∇ u |, but without assuming the sign condition. The right-hand sidef belongs toL 1 ( Ω ) .